Hacia el traductor de La zucca del doni en Spañol - Capra, Daniela (Analecta Malacitana. Revista de la sección de Filología de la Facultad de Filosofía y Letras, 2018)
RESUMEN: La Zucca del Doni en Spañol (1551) se publicó tan solo cuatro meses después de la princeps de la Zucca doniana. El traductor es anónimo, pero la calidad del texto traducido, algunas peculiaridades suyas y la fuerte personalidad que el traductor deja entrever nos han inducido a intentar un acercamiento a esta ? gura para dibujar su per? l. Con este propósito investigamos tanto unos datos externos como otros internos al texto, de los cuales emerge una ? gura de hombre culto y sumamente ortodoxo en cuestiones religiosas. ABSTRACT: The Spanish translation of A. F. Doni’Zucca (1551) was published just four months after the Italian editio princeps by the same printer; the translator remained anonymous, in spite of the fact that he shows a strong personality, emerging from the pages of his dedication and from the translation itself. It is our pourpose to approach his portrait, following the traces that he left in is work, but also collecting some extra-textual data. It will emerge the ? gure of a cultivated person, with a deep knowledge of the Holy Scripture and a strong sense of religion.